HISTORY AND DEVELOPMENT OF LEGAL INERPRETATION IN JAPAN ON THE BASIS OF THE SO CALLED TOKYO TRIAL - HORIE, Yuki (Comparative Legilinguistics, 2013)
The International Military Tribunal for the Far East, the so called Tokyo Trial is the international trial of the war criminals who led the Japanese government and military during the Second World War. The trial began on 3rd of May 1946 and closed on 11th of November 1984. Around the same time in Europe the Nuremberg Trial of Nazi war crimes was conducted. In both trials the role of the interpreter was essential, for example, in the Nuremberg Tribunal the simultaneous interpreting in English, German, French and Russian was applied. On the other hand in the Tokyo Trial, though the Japanese, the English and other languages as the Chinese were used during the trial, the position of the interpreters was not emphasized enough. The aim of this paper is to analyze the basic theory of interpreting in comparison with the interpreters’ role in both trials.